2008
DOI: 10.1002/ceat.200700510
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into Photocatalytic Degradation of Gaseous Benzene in a Circulated Photocatalytic Reactor (CPCR)

Abstract: Due to the fact that suspended TiO 2 powder enjoys free contact with gaseous pollutant molecules in photocatalytic reactors, it can generally achieve better efficiency than immobilized TiO 2 catalysts. However, difficulties with the separation of this catalyst powder from treated pollutants and its re-use often limit its application. Therefore, a circulated photocatalytic reactor (CPCR) was designed to enhance the performance of the photocatalytic degradation of gaseous benzene. TiO 2 film photocatalysts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The decomposition of trace contaminants from polluted air using a photocatalytic reactor system has been investigated extensively in the last three decades. It has been demonstrated that photocatalytic oxidation is a complete and efficient remediation technology in a broad range of pollutants under certain operating conditions at ambient temperature and pressure without any chemical additives. Furthermore, the nanosemiconductor TiO 2 , employed extensively as a photocatalyst, is inexpensive, safe, and very stable with a high photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The decomposition of trace contaminants from polluted air using a photocatalytic reactor system has been investigated extensively in the last three decades. It has been demonstrated that photocatalytic oxidation is a complete and efficient remediation technology in a broad range of pollutants under certain operating conditions at ambient temperature and pressure without any chemical additives. Furthermore, the nanosemiconductor TiO 2 , employed extensively as a photocatalyst, is inexpensive, safe, and very stable with a high photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Since the photocatalytic degradation of gaseous benzene in the CPCR has already been investigated [7], the nano-TiO 2 film photocatalyst supported on the inner wall of the quartz glass tube in the CPCR was expected to perform well in the photodegradation of the benzene-toluene mixture. One can derive two conclusions from Fig.…”
Section: Influence Of the Mixture Concentrations Of Benzene And Toluementioning
confidence: 99%
“…Many researchers reported that the adsorption of gas follows the Langmuir isotherm [7,15,16] isotherms for the gaseous mixture of benzene and toluene on the catalyst film for 1 h in darkness conditions, under circulation conditions for the mixture concentrations of benzene and toluene at 0.12 and 0.60 mmol L -1 with different proportions in the CPCR, respectively, have been studied.…”
Section: Adsorptions Of Benzene and Toluenementioning
confidence: 99%
See 2 more Smart Citations